Exploring the Emerging Careers: Opportunities Beyond Traditional Career Paths in a Gig Economy - Solanki, Kalpana (Archives of Business Research, 2025)
Making a feasible career choice plays a key role in career goal advancement and achievement for all the professionals. This research study aims to explore the new career opportunities which are different from the traditional careers. This research will use a qualitative data through primary (interviews) and secondary data collection. This research is an attempt to explore the feasibility of the modern career choices beyond the traditional career paths and their viability as a full time long term career choice by aspirants.